Pharyngeal Gonococcal Infections: A Cross-Sectional Study in a Network of Sexually Transmitted Disease Clinics; Sexually Transmitted Disease Surveillance Network—January 2016 to June 2018. Issue 12 (December 2019) - Llata, Eloisa; Braxton, Jim; Asbel, Lenore; Huspeni, Dawn; Hsu, Katherine; Kerani, Roxanne P.; Nguyen, Trang Quyen; Pathela, Preeti; Schumacher, Christina; Toevs, Kim; Torrone, Elizabeth
Abstract : Abstract: We conducted a cross-sectional analysis using sexually transmitted disease clinic data to determine test of cure rates among persons diagnosed with pharyngeal gonococcal infections who were treated with a nonceftriaxone, nonazithromycin therapy. Less than 10% returned for a test of cure, highlighting the need to understand factors that can lead to improved compliance. Abstract : Test of cure was documented in less than 10% of sexually transmitted disease clinic patients diagnosed with pharyngeal gonococcal infection treated with nonceftriaxone, nonazithromycin regimens, but continued efforts are warranted to optimize compliance.Supplemental digital content is available in the text.